PERANCANGAN SISTEM MONITORING SUHU DAN KADAR AIR PAKAN IKAN PADA PURWARUPA PENGERING PAKAN IKAN MENGGUNAKAN VISUAL STUDIO - Zulkarnain, Zulkarnain; Triwiyatno, Aris; Sudjadi, Sudjadi (Transient: Jurnal Ilmiah Teknik Elektro, 2018)
Fish feed dryer in the FPIK Lab (Faculty of Fisheries and Marine Sciences) Diponegoro University still uses manual monitoring so it is less effective. Therefore, a good monitoring is needed to deal with problems in the fish feed dryer in the FPIK UNDIP Lab. In this Final Project designed a temperature and water content monitoring system using LCD and Visual Studio applications. In this Final Project there are 3 tests including LCD testing, Visual Studio form, and alarm testing. The results of monitoring the temperature data and water content of fish feed on the prototype of fish feed dryer through LCD and Visual Studio form successfully went well with the reading delay through Visual Studio by 1 second. Ready feed alarm testing has been successfully carried out when humidity reaches 10% RH and moisture content is 10%. Overheat alarm testing has been performed when the temperature reaches 5 Â° C above the given setpoint for 10 seconds. And the below setpoint test was successful when the temperature did not reach the setpoint in the range of 5 Â° C below the given setpoint.